An evolutionary framework outlining the integration of individual social and spatial ecology. (27th November 2017) - Webber, Quinn M. R.; Vander Wal, Eric
Abstract: Behaviour is the interface between an organism and its environment, and behavioural plasticity is important for organisms to cope with environmental change. Social behaviour is particularly important because sociality is a dynamic process, where environmental variation influences group dynamics and social plasticity can mediate resource acquisition. Heterogeneity in the ecological environment can therefore influence the social environment. The combination of the ecological and social environments may be interpreted collectively as the "socioecological environment, " which could explain variation in fitness. Our objective was to outline a framework through which individual social and spatial phenotypes can be integrated and interpreted as phenotypes that covary as a function of changes in the socioecological environment. We propose the socioecological environment is composed of individual behavioural traits, including sociality and habitat selection, both of which are repeatable, potentially heritable and may reflect animal personality traits. We also highlight how ecological and social niche theory can be applied to the socioecological environment framework, where individuals occupy different socioecological niches. Individual sociality and habitat selection are also density‐dependent, and theory predicts that density‐dependent traits should affect reproduction, survival, and therefore fitness and population dynamics. We then illustrate the proximate links between sociality, habitat selection and fitness as well as the ultimate, and possibly adaptive, consequences associated with changes in population density. The ecological, evolutionary and applied implications of our proposed socioecological environment framework are broad and changes in density could influence individual fitness and population dynamics. For instance, human‐induced environmental changes can influence population density, which can affect the distribution of social and spatial phenotypes within a population. In summary, we outline a conceptual framework that incorporates individual social and spatial behavioural traits with fitness and we highlight a range of ecological and evolutionary processes that are likely associated with the socioecological environment. Abstract : The authors integrate the ecological and evolutionary implications of individual social and spatial behaviour as the "socioecological environment." They discuss the role of animal personality, nice theory, quantitative genetics and eco‐evolutionary dynamics through the lens of the "socioecological environment."